President DiBiaggio with past presidents of Michigan State University - Unknown (Tufts Archival Research Center, 2005)
14 x 9.5. Original photo undated. This photograph was originally published in the MSU News-Bulletin on November 16, 1989 and is credited to Bruce Cox. The caption for the photo in that issue reads "'Past and Present Leaders' Five former MSU presidents joined President DiBiaggio Nov. 9 in a private ceremony for the unveiling of their portraits in the Board Room of the Administration Building. From left are Edgar Harden, president from 1978-1979; DiBiaggio, president since 1985; John Hannah, 1941-1969; Clifton Wharton Jr., 1970-1978; Cecil Mackey, 1979-1985; and Walter Adams, 1969-1970."